2011
DOI: 10.1155/2011/213783
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectroscopy for Clinical Oncology

Abstract: Cancer is one of the leading causes of death throughout the world. Advancements in early and improved diagnosis could help prevent a significant number of these deaths. Raman spectroscopy is a vibrational spectroscopic technique which has received considerable attention recently with regards to applications in clinical oncology. Raman spectroscopy has the potential not only to improve diagnosis of cancer but also to advance the treatment of cancer. A number of studies have investigated Raman spectroscopy for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 134 publications
0
61
0
Order By: Relevance
“…As described above, near-infrared Raman scattering has been used for the in vivo detection of cancer with high molecular sensitivity (108). However, as Raman scattering is a weak process, the acquisition times of single spectra are in the range of seconds to tens of seconds.…”
Section: Multiscale Imagingmentioning
confidence: 99%
“…As described above, near-infrared Raman scattering has been used for the in vivo detection of cancer with high molecular sensitivity (108). However, as Raman scattering is a weak process, the acquisition times of single spectra are in the range of seconds to tens of seconds.…”
Section: Multiscale Imagingmentioning
confidence: 99%
“…[32,[34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] In 1998, a fiberoptic in vivo Raman study of cervix to delineate precancer lesions from the normal cervix was reported. [39] In this study, in vivo Raman spectra of cervix could be acquired in 90 s. Authors concluded that the increase in the laser power could reduce the integration time to less than 20 s for measuring in vivo Raman spectra of cervix.…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…Another statistical method, partial least squares, was used to assign a chemical composition to cancerous tissue in 2005 (19), from a known database of constituents. Because spectroscopy is not the main thrust of this review, the reader is directed toward a review of Raman spectroscopy for cancer diagnosis (20). Most Raman spectroscopy cancer diagnosis is performed on ex vivo tissue but has also been extended to blood serum (21).…”
Section: Raman Spectroscopy Of Cancer Tissuesmentioning
confidence: 99%